Preoperative Alcohol Use Disorder Associated with Increased Complications, Readmission, and Cost Following Ankle Arthrodesis - Weston E. McDonald BS; Joshua L. Morningstar BS; Sarah Jenkins MD; Christopher E. Gross MD; Daniel J. Scott MBA, MD (Foot & Ankle Orthopaedics)
Category: Ankle; Ankle Arthritis Introduction/Purpose: Alcohol use disorder (AUD) has been estimated to affect approximately 11% of adults and is associated with increased morbidity, social consequences, and financial burden. A number of studies in orthopaedic spine and arthroplasty literature have indicated patients with preoperative AUD to be at increased risk for adverse outcomes, increased length of stay, and increased cost of procedure. However, there is a paucity of literature examining the effect of preoperative AUD on the outcomes of patients undergoing ankle arthrodesis (AA). The purpose of this study is to evaluate the influence of AUD on postoperative outcomes following AA. Methods: The Nationwide Readmissions Database (NRD) was queried from 2016-2020 to identify 26,705 patients undergoing primary elective AA as identified by International Classification of Diseases, Tenth Revisions (ICD-10), Procedure coding system (PCS) codes for ankle arthrodesis (OSGFXXX, OSGGXXX). Patients were divided into two cohorts based on the presence of preoperative alcohol use disorder, as identified by ICD-10 clinical modification (CM) codes, with 612 (2.29%) being diagnosed with AUD. Preoperative demographics, comorbidities, postoperative outcomes, cost of admission, and total length of stay (LOS) were analyzed between cohorts. Multivariate regression analyses were conducted to identify independent predictors of postoperative outcomes other than preoperative AUD. The overall cohort was majority male (51.0%) with mean age of 57.31±16.15 years, and Charlson-Deyo Comorbidity Index (CCI) score of 1.56±2.00. Results: Patients identified with preoperative AUD were statistically significantly younger (AUD=55.14 years; non-AUD=57.29 years; p<.001), male (AUD=75.3%, non-AUD=50.3%; p<.001), from the lowest income quartile (AUD=34.6%, non-AUD=27.3%; p<.001), more likely to have Medicaid insurance (AUD=30.7%, non-AUD=13.9%; p<.001), and had a significantly higher rate of multiple comorbidities, individually and as measured by CCI (AUD=2.07, non-AUD=1.55; p<.001). Multivariate regression analysis of 180-day postoperative outcomes found that preoperative AUD was significantly predictive of 22% increased risk of any complication (Odds ratio [OR]=1.217; p=.035), 42% increase in risk of readmission (OR=1.424; p<.001), and 135% increase in risk of extended LOS >4 days (OR=2.349; p<.001), among other specific complications listed in Table 1. Further, preoperative AUD is significantly predictive of nearly $7,000 increase in total cost of procedure (β=6,929.34; p<.001). Conclusion: Alcohol use disorder is associated with significantly increased perioperative morbidity in patients undergoing ankle arthrodesis. When controlling for differences in comorbid conditions, this study found preoperative AUD was significantly predictive of statistically significantly higher rates of postoperative complications, readmissions, and adverse discharge within 180-days of primary procedure as well as increased LOS, and a substantially higher cost of procedure following AA. Physicians should consider this risk factor when identifying patients and tailoring medication regimens for patients receiving ankle arthrodesis.